Identification of Fangjihuangqi Decoction as a late-stage autophagy inhibitor with an adjuvant anti-tumor effect against non-small cell lung cancer - Qiugu Chen; Yuan Liao; Yujiao Liu; Yue Song; Junbo Jiang; Zhen zhang; Anqi Li; Mengyi zheng; Xiaoyi Chen; Tingxiu Zhao; Jiangyong Gu; Yuhui Tan; et al. (BMC, 2023)
Abstract Background Clinically, although chemotherapy is one of the most commonly used methods of treating tumors, chemotherapeutic drugs can induce autophagic flux and increase tumor cell resistance, leading to drug tolerance. Therefore, theoretically, inhibiting autophagy may improve the efficacy of chemotherapy. The discovery of autophagy regulators and their potential application as adjuvant anti-cancer drugs is of substantial importance. In this study, we clarified that Fangjihuangqi Decoction (FJHQ, traditional Chinese medicine) is an autophagy inhibitor, which can synergistically enhance the effect of cisplatin and paclitaxel on non-small cell lung cancer (NSCLC) cells. Methods We observed the changes of autophagy level in NSCLC cells under the effect of FJHQ, and verified the level of the autophagy marker protein and cathepsin. Apoptosis was detected after the combination of FJHQ with cisplatin or paclitaxel, and NAC (ROS scavenger) was further used to verify the activation of ROS-MAPK pathway by FJHQ. Results We observed that FJHQ induced autophagosomes in NSCLC cells and increased the levels of P62 and LC3-II protein expression in a concentration- and time-gradient-dependent manner, indicating that autophagic flux was inhibited. Co-localization experiments further showed that while FJHQ did not inhibit autophagosome and lysosome fusion, it affected the maturation of cathepsin and thus inhibited the autophagic pathway. Finally, we found that the combination of FJHQ with cisplatin or paclitaxel increased the apoptosis rate of NSCLC cells, due to increased ROS accumulation and further activation of the ROS-MAPK pathway. This synergistic effect could be reversed by NAC. Conclusion Collectively, these results demonstrate that FJHQ is a novel late-stage autophagy inhibitor that can amplify the anti-tumor effect of cisplatin and paclitaxel against NSCLC cells.